Pengembangan Media Evaluasi Bahasa Arab QuizWhizzer pada Materi As-Shihah Bagi Siswa Kelas XI MA Unggulan K.H. Abd. Wahab Hasbulloh - Muhammad Jaddul Haq; Asma Salwa Salsabila; Lailatul Qomariyah; Imamah Nurun Najah; Binti Muslikah (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2026)
The objective of this research is to create a QuizWhizzer-based assessment tool in Arabic for the Ash-Shihhah subject, intended for eleventh-grade pupils at MA Unggulan K. H. Abd. Wahab Hasbulloh. The ADDIE model, encompassing analysis, design, development, implementation, and assessment phases, is the framework used for the creation of this tool. The media is designed to align with student needs, curriculum requirements, and the characteristics of the learning material. The implementation was carried out in the classroom through interactive evaluation activities presented in the form of an educational game. The results show that QuizWhizzer successfully increased students’ motivation and engagement, and significantly improved their learning outcomes. This improvement is evidenced by an N-Gain Score of 0.7838, categorized as high, and an N-Gain percentage of 78.38%, categorized as effective. Additionally, the media provides a more meaningful learning experience by encouraging active participation, independent work, and healthy competition among students. Therefore, QuizWhizzer is effective as an interactive evaluation tool in Arabic language learning, particularly for the Ash-Shihhah material.